Perceptions of Drug Abuse Among Students: Sociocultural Influences, Awareness, and Misconceptions - Pujari, Ritu; Bansal, Dr Garima; Sharma, Renu; Sahi, Disha (Journal of Neonatal Surgery, 2025)
Drug abuse among students is a growing public health problem that leads to significant psychological, academic, and social effects. Even though people are more aware of the dangers of drugs, relaxed attitudes, perceived social benefits, and academic pressures still encourage both experimentation and regular use. This review compiles evidence related to students perceptions of substance abuse, emphasizing sociocultural factors, levels of awareness, and enduring misconceptions. A narrative methodology was employed to examine studies from PubMed, Scopus, Web of Science, and Google Scholar published between 2010 and 2024. Findings suggest that although many students are cognizant of health risks, they often perceive alcohol and cannabis as relatively benign or typical, while sedatives and stimulants are frequently misused to manage exams and stress. Factors such as gender differences, stigma, and variations concerning the type of institution and urban settings also influence perceptions and behaviors. Successful responses include comprehensive prevention programs that integrate skill development, peer-led initiatives, family involvement, and accessible confidential counseling and addiction recovery services on campuses. The review underscores the potential for culturally appropriate, evidence-driven interventions and identifies areas for future research, including longitudinal studies and thorough evaluations of digital prevention methods